Practices And Experiences Of Malaysian In-Service English Language Teachers’ Professional Development Using Social Media - Thomas, Anita Jesmin Albert David (2021)
With the advent of learning communities, social media is becoming a far more popular and convenient platform for teachers’ professional development. It is mainly due to the capacity of social media to connect teachers from various geographical areas, as well as its ability to transcend time. Nevertheless, as the literature indicates, not much is known in terms of teachers’ uses of social media for professional development purposes. This study examines English Language teachers’ (n = 1000) practices and experiences of using social media as a platform to initiate and enhance ones’ professional development. Six social media platforms were examined in this study mainly Facebook, Instagram, Twitter, YouTube, WhatsApp, and Telegram. Quantitative method (online questionnaire) and qualitative method (interview via Telegram) were used to investigate and determine the usefulness of social media to the English Language teachers nationwide. The online questionnaire was designed with multiple-choice, open-ended, and Likert-type questions to assess in-service English Language teachers’ practices and experiences of using social media for professional development. Interview sessions via Telegram complemented and contributed important insights to this study. This study also established that 98.70 % of the English Language teachers use the smartphone to connect to the internet because it is convenient. This is proven true as the online survey was done using one of the devices. The MOE has also aided 430,000 teachers with free tablets and 138,820 Altitude smartphones by Yes 4G so that teachers could get connected to the internet. Several implications and contributions of the study were also highlighted. The findings revealed that the usage of social media among English Language teachers are high and Telegram was ranked as the most beneficial social media for teachers’ professional development. Most of the participants agree that social media has benefitted their professional development growth.